THE INFLUENCE OF COMPENSATION, WORK DISCIPLINE, AND ENVIRONMENT WORK ON EMPLOYEE PERFORMANCE AT PT. LOTUS BOGA LIMA IN BOGOR - Eri Wulansari; Sudarijati Sudarijati; Samsuri Samsuri (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Human resources (HR) are a crucial factor in achieving company goals. Strong HR capabilities are reflected in strong performance and serve as an asset to the company. Therefore, management needs to prioritize effective HR management to improve organizational effectiveness and efficiency. This study aims to determine the effect of compensation, work discipline, and the work environment on employee performance at PT. Lotus Boga Lima. A non- probability sampling technique with saturated sampling was used as the sample. Multiple linear regression analysis was used to analyze the impact of compensation, work discipline, and the work environment on employee performance, both simultaneously and partially. Compensation is the most dominant factor influencing employee performance at PT. Lotus Boga Lima. Therefore, the company needs to pay attention to and improve employee compensation to improve employee performance.